Repurposing Artemisinin and its Derivatives as Anticancer Drugs: A Chance or Challenge? - Ma, Zhaowu; Woon, Clariis Yi-Ning; Liu, Chen-Guang; Cheng, Jun-Ting; You, Mingliang; Sethi, Gautam; Wong, Andrea Li-Ann; Ho, Paul Chi-Lui; Zhang, Daping; Ong, Peishi; Wang, Lingzhi; Goh, Boon-Cher (Frontiers in Pharmacology, 2021)
Cancer has become a global health problem, accounting for one out of six deaths. Despite the recent advances in cancer therapy, there is still an ever-growing need for readily accessible new therapies. The process of drug discovery and development is arduous and takes many years, and while it is ongoing, the time for the current lead compounds to reach clinical trial phase is very long. Drug repurposing has recently gained significant attention as it expedites the process of discovering new entities for anticancer therapy. One such potential candidate is the antimalarial drug, artemisinin that has shown anticancer activities in vitro and in vivo. In this review, major molecular and cellular mechanisms underlying the anticancer effect of artemisinin and its derivatives are summarised. Furthermore, major mechanisms of action and some key signaling pathways of this group of compounds have been reviewed to explore potential targets that contribute to the proliferation and metastasis of tumor cells. Despite its established profile in malaria treatment, pharmacokinetic properties, anticancer potency, and current formulations that hinder the clinical translation of artemisinin as an anticancer agent, have been discussed. Finally, potential solutions or new strategies are identified to overcome the bottlenecks in repurposing artemisinin-type compounds as anticancer drugs.